2017
DOI: 10.1002/1873-3468.12562
|View full text |Cite
|
Sign up to set email alerts
|

Cushing's syndrome mutant PKAL205R exhibits altered substrate specificity

Abstract: The PKAL205R hotspot mutation has been implicated in Cushing’s Syndrome through hyperactive gain-of-function PKA signaling, however its influence on substrate specificity has not been investigated. Here, we employ the Proteomic Peptide Library (ProPeL) approach to create high-resolution models for PKAWT and PKAL205R substrate specificity. We reveal that the L205R mutation reduces canonical hydrophobic preference at the substrate P+1 position, and increases acidic preference in downstream positions. Using these… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…This suggests that this approach can successfully identify residues that are of relevance for the functional divergence of kinases. Of these residues, 8 have been implicated in determining differences in kinase specificity: domain position 84 [32–34], 86 [35], 144 [16,36,37], 157 [37,38], 158 [35,37], 162 [35], 164 [39,40], and 205 [35]. The number of substitutions for ‘proximal’ residues is generally higher than that for residues without an assigned function (Mann-Whitney, one-tailed, p = 3.2 × 10 −6 ).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that this approach can successfully identify residues that are of relevance for the functional divergence of kinases. Of these residues, 8 have been implicated in determining differences in kinase specificity: domain position 84 [32–34], 86 [35], 144 [16,36,37], 157 [37,38], 158 [35,37], 162 [35], 164 [39,40], and 205 [35]. The number of substitutions for ‘proximal’ residues is generally higher than that for residues without an assigned function (Mann-Whitney, one-tailed, p = 3.2 × 10 −6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another mutation leading to Cushing’s syndrome in the Cα subunit of PKA is L205R [ 56 ], which disrupts the intramolecular allosteric network [ 65 ]. Consequently, PKA C L205R has a decreased catalytic efficiency for Kemptide and phosphorylates non-canonical substrates leading to a dysregulated signaling network in tumor cells [ 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have curated a master negative control list (Lubner et al, 2017), which was generated by pooling phosphopeptides previously identified in negative control experiments (Chou et al, 2012), previously identified endogenous E. coli phosphorylation sites (Macek et al, 2008; Soares et al, 2013), and phosphorylation sites identified in empty vector and kinase dead negative control experiments. This list is available as Supplementary Table S1.…”
Section: Basic Protocolmentioning
confidence: 99%
“…Using our lab’s suite of computational tools, we can extract and visualize kinase specificity motifs, and make high-confidence predictions of downstream targets. ProPeL can also be used to evaluate the influence of disease-associated mutations on kinase substrate specificity (Lubner et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation